2011
DOI: 10.1519/jsc.0b013e318212e20f
|View full text |Cite
|
Sign up to set email alerts
|

Throwing Velocities, Anthropometric Characteristics, and Efficacy Indices of Women's European Water Polo Subchampions

Abstract: Water polo is a team sport characterized by a high-intensity, intermittent activity, where technical and tactical aspect are of a great importance. For that reason, the main aim of this study was to define the anthropometrical characteristics, maximum isometric grip strength, training and competition throwing velocities, and the efficacy indices in female high-level water polo players. A second purpose was to examine the differences between the throwing velocities in training vs. European championships in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…This may be because these latter situations are common in the course of the evenly balanced games corresponding to the final phase of championships. For this reason, in addition to developing aerobic endurance-the average distance swum in a game is greater than 1300 m (16)-it is necessary to increase shooting speed in situations of equality because this has to be greater than in situations of superiority or counterattack (1). It has to be borne in mind that in counterattacks, the swimming speed of the players produces situations of imbalance in the transition (defense-attack) (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because these latter situations are common in the course of the evenly balanced games corresponding to the final phase of championships. For this reason, in addition to developing aerobic endurance-the average distance swum in a game is greater than 1300 m (16)-it is necessary to increase shooting speed in situations of equality because this has to be greater than in situations of superiority or counterattack (1). It has to be borne in mind that in counterattacks, the swimming speed of the players produces situations of imbalance in the transition (defense-attack) (23).…”
Section: Discussionmentioning
confidence: 99%
“…W ater polo was the first Olympic team sport (in Paris, 1900), but research on water polo is fairly recent (43), and focused on specific aspects (in alphabetical order): biomechanical (9), kinanthropometric (1,2,6,13,27), physical fitness evaluation (13,14,48), physiological (20,36,43,47), and training (16,22,29). For example, some studies have shown that the front crawl technique used to move from one point to another can vary depending on the objectives that correspond to the particular moment of training or situation in the match (9).…”
Section: Introductionmentioning
confidence: 99%
“…It allows us to cautiously compare our results with studies conducted under laboratory conditions. However, it is important to note that while Alcaraz et al (2011) found that elite players modified their shot pattern and speed depending on whether they were in training or competition conditions, a previous study did not observe such a difference. Therefore, it is impossible to compare our results with previous studies because of conflicting results, as well as the fact that these were performed under experimental conditions and did not consider analysis of a real game.…”
Section: Discussionmentioning
confidence: 78%
“…[15] The demographic characteristics seen in the 15 female clublevel water polo players are comparable to other research on elite water polo players of a similar age. [16] The majority of the participants presented with a forward head and rounded shoulder posture while nine also had slight thoracic spine kyphosis. These are common postures in swimmers and overhead athletes where they present with shortened cervical extensors and lengthened cervical flexors.…”
Section: Discussionmentioning
confidence: 96%